In the House of Representatives, April 19, 1776. Whereas sundry persons of this colony have joined our unnatural enemies ... Resolved that the committee of correspondence, safety and inspection, in each and every town ... where there is any real or personal estate ... immediately take possession of all such estates . (LLMC-digital (Series), 1776)
April 23, 1776 resolutions regarding the procedure for seizing real and personal property belonging to loyalists.